Correlation of the expression of hyaluronan and CD44 with the presence of gingival inflammatory infiltrate in advanced generalized periodontitis - Ćavar, Ivna (Array, 2020)
To investigate the association between the expression of hyaluronan (HA) and its main receptor CD44 with the presence of inflammatory infiltrate in gingiva samples of patients suffering from advanced generalized periodontitis. Material and Methods: Samples of gingival tissue from healthy donors (controls, n = 20) and patients suffering from advanced generalized periodontitis stage 3 and 4 (test group, n = 20) were obtained. For immunofluorescence (IF) staining, primary antibodies against HA, CD44 and general inflammatory cell marker CD45 were used. The microscopic slides were photographed and panoramic images were edited in Adobe Photoshop®. The quantification of IF signal expression domains and spatial gradients was performed in ImageJ. The Microsoft Office Excel 2016 and GraphPad v8 software ware used for statistical analysis. Results: HA and CD44 were found to be widely expressed in the epithelium and subepithelial stroma of both healthy and diseased gingiva, including the areas of the gingiva containing the inflammatory infiltrate. No difference in the total expression of HA and CD44 in healthy and diseased gingiva was found. However, the pattern of distribution of HA and CD44 signals was somewhat different between the two groups of samples with regard to a statistically significant increase in stromal expression of HA and CD44 in diseased gingiva compared to healthy gingiva. No spatial correlation between HA and CD44 expression with the presence of inflammatory infiltrate was found in diseased gingiva. Moderate spatial correlation between HA and CD44 was found in diseased gingiva. Conclusion: HA and CD44 might play a role in the regulation of inflammatory response in advanced generalized periodontitis. However, further studies are needed in order to properly characterize such role of both investigated factors.